Geochemistry of the Laiyang Group from outcrops and Lingke-1 core on Lingshan Island, Shandong Province, Eastern China: implications for provenance, tectonic setting and palaeo-environment. (2nd January 2022) - Ma, Qing; Zhou, Yaoqi; Mu, Hongyu; Zhou, Tengfei; Zhao, Hanjie; Yin, Xingcheng; Liu, Yanzi
Abstract: Lower Cretaceous sedimentary rocks of Lingshan Island, located along the continental margin of East Asia, have received increased attention. The Lingke-1 core mainly belongs to the Lower Cretaceous Laiyang Group. We investigate provenance, tectonic setting, palaeoclimate and palaeoredox conditions in the study area using elemental geochemistry, thereby elucidating the depositional history of the Lower Cretaceous sediments and reconstructing the palaeo-environment. To achieve this, 90 siltstones and 76 mudstones were sampled from this core and other outcrops on Lingshan Island. The chemical index of alternation (CIA) values for the majority of the samples and the bivariate diagrams indicate that the sedimentary rocks were subjected to minor weathering processes. Geochemical results suggest that source rocks for the region are felsic igneous and metamorphic rocks, along with minor proportions of intermediate igneous rocks. Major- and trace-element discrimination diagrams, deciphering the tectonic history, indicate that source rocks mainly originated from the continental island-arc and active continental margin. Several representative geochemical indices and the bivariate plots based on elemental contents show that the Laiyang Group was predominantly deposited in arid conditions. Sr/Ba values suggest a palaeosalinity transition from brackish to saline, demonstrating a depositional transformation from lacustrine facies for the lower Laiyang Group to marine facies in the upper Laiyang Group. U/Th and V/(V+Ni) ratios and Ce anomalies in the rocks indicate anoxic conditions. We conclude that the conspicuous decline in the trends of the above three geochemical indices, ranging between 400 and 800 m, may be related to the latest Hauterivian oceanic anoxic event.